A COMPARISON OF THE WATER ABSORPTION AND WATER SOLUBILITY VALUES OF FOUR DIFFERENT COMPOSITE RESIN MATERIALS - Cangül, Suzan; Adıgüzel, Özkan; Tekin, Samet; Öztekin, Faruk; Satıcı, Ömer (My University, 2018)
Objectives: The aim of this study was to compare thewater absorption and water solubility of four differentcomposte resin materials.Materials and Methods: A total of 40 cylindrical discswere prepared and polymerised with light, as 10 fromeach group, each sample 2 mm in depth and 8 mm indiameter. The samples were kept for 24 hrs in adessicator until a stable weight was reached. Then, theweight of each sample was measured on highly sensitivescales. To calculate the water absorption and solubility,measurements were made again with the sensitive scalesat the end of 1, 7 and 30 days. The data obtained wereevaluated with One-Way ANOVA variance analysis andthe Friedman test.Results: As a result of the statistical analyses, significantdifferences were determined between the compositeresins in respect of water absorption on days 7 and 30 andin respect of solubility on day 30 only (p<0.05).Conclusion: When the water absorption and watersolubility of composite resins at the end of 30 days wereevaluated statistically, it was observed that Ceram X Onematerial showed the lowest values. This is related to thestructure of the restorative material.It can be concluded that the negative mechanical,physical and biological effects created by the waterabsorption and water solubility factors of restorativematerials are important issues that should be taken intoconsideration.
Keywords: Diş Hekimliği